2011
DOI: 10.1093/scan/nsr075
|View full text |Cite
|
Sign up to set email alerts
|

Breakdown in the brain network subserving moral judgment in criminal psychopathy

Abstract: Neuroimaging research has demonstrated the involvement of a well-defined brain network in the mediation of moral judgment in normal population, and has suggested the inappropriate network use in criminal psychopathy. We used functional magnetic resonance imaging (fMRI) to prove that alterations in the brain network subserving moral judgment in criminal psychopaths are not limited to the inadequate network use during moral judgment, but that a primary network breakdown would exist with dysfunctional alterations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
111
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(128 citation statements)
references
References 39 publications
9
111
1
2
Order By: Relevance
“…Interpersonal psychopathic traits additionally related to stronger CMA connectivity with a network of cortical midline structures growingly implicated in psychopathy [Anderson and Kiehl, 2012; Philippi et al, 2015; Pujol et al, 2012], which extended from the precuneal and posterior cingulate cortices to rostral and ventral portions of the medial prefrontal territory. Notwithstanding their myriad functions, these interconnected cortical regions seem to serve as key nodes within the so‐called default mode network (DMN), whose network function putatively supports internally and externally directed sociocognitive processes [Andrews‐Hanna et al, 2010; Li et al, 2014].…”
Section: Discussionmentioning
confidence: 99%
“…Interpersonal psychopathic traits additionally related to stronger CMA connectivity with a network of cortical midline structures growingly implicated in psychopathy [Anderson and Kiehl, 2012; Philippi et al, 2015; Pujol et al, 2012], which extended from the precuneal and posterior cingulate cortices to rostral and ventral portions of the medial prefrontal territory. Notwithstanding their myriad functions, these interconnected cortical regions seem to serve as key nodes within the so‐called default mode network (DMN), whose network function putatively supports internally and externally directed sociocognitive processes [Andrews‐Hanna et al, 2010; Li et al, 2014].…”
Section: Discussionmentioning
confidence: 99%
“…Although the term psychopathy is not applied to adolescents, high levels of psychopathic traits are nevertheless associated with an increased risk of violent offending in participants with CD, 31,32 and CD with elevated psychopathic traits has been suggested to represent a more pervasive subtype of CD 33 . A number of studies have reported reduced connectivity between brain regions overlapping with core DMN midline regions in psychopathic adults 34,35 . Interestingly, even within the construct of psychopathy, there are possibly differential effects of the affective/interpersonal and antisocial factors of psychopathy, with the affective/interpersonal factor associated with decreased medial-lateral DMN connectivity and the antisocial factor associated with increased connectivity between prefrontal and parietal DMN components 36 .…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…This finding contradicts earlier evidence from adult prisoners that has demonstrated lower DMN connectivity in individuals with high levels of psychopathic traits relative to typically-developing adults. For example, Pujol et al 34 compared prisoners with high levels of psychopathic traits with healthy controls, and Motzkin et al 35 compared prisoners with high versus low levels of psychopathy. Both studies found connectivity between anterior and posterior midline components of the DMN were reduced in psychopathic individuals compared with control participants.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…As with any medical intervention -and we believe an invasive intervention in the brain should be considered as such -the treating physician or psychologist is responsible for ensuring the quality of care. 12 Treatments consisting of direct interventions in the brain should be considered as a 'global treatment'; it does not only focus on the brain but on the whole person in interaction with his environment [40]. The treatment consist not only of the actual operation, but includes the fine-tuning of the electric parameters as well as the 11 Because direct neuromodulation affects the entire brain (by directly stimulating part of a network in the brain that interacts with other areas and networks in the brain) subsequent psychological and personality changes may either go unnoticed by the individual in question and leave the individual without any means to reflect upon, or rationally endorse, her changed identity, or may lead one to unreflectively accept or welcome certain traits.…”
Section: 'Concealed' Narrative Identity Changesmentioning
confidence: 99%
“…If we take into account the way our brain works it is not unlikely that directly changing an individual's moral dispositions (e.g., empathy, sense of justice, sense of fairness) will affect one's entire belief system, i.e., in such a way that the individual in question does not necessarily experience a discontinuity as such. 12 We are aware that some interventions, such as transcranial direct current stimulation (tDCS), can currently be applied on a do-ityourself basis, hence without a responsible medical practitioner in charge. For reasons of patient safety and well-being, we would recommend that such interventions are regulated by legal measures for product safety and personal use (e.g., licenses for personal use involving training sessions with skilled experts) in the short-term while undergoing regulation by the Medical Devices Directive (MDD) in the long term [53].…”
Section: 'Concealed' Narrative Identity Changesmentioning
confidence: 99%